Transformasi metodologi pendidikan Islam melalui integrasi PjBL dan Critical Pedagogy Islami - Ramadhan, Rizal Ilham; Mujahidin, Endin; Lisnawati, Santi (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
This research aims to develop an Islamic learning methodology design through the integration of Project-Based Learning (PjBL) with Islamic Critical Pedagogy. The study employed a literature review method with a descriptive qualitative approach, analyzing the theories, characteristics, and application of both approaches in the context of Islamic education. The results indicate that PjBL increases student engagement in solving real-world problems, while Islamic Critical Pedagogy fosters critical awareness grounded in spiritual values and etiquette. The integration of the two creates participatory, transformative learning that is relevant to the needs of the 21st century. The case study of "Bumi Amanah Allah" demonstrates the effectiveness of this model in fostering environmental awareness based on Qur'anic values. This research contributes to offering a new methodological framework for the development of contemporary Islamic education. Abstrak Penelitian ini bertujuan mengembangkan desain metodologi pembelajaran Islam melalui integrasi Project-Based Learning (PjBL) dengan Critical Pedagogy Islami. Penelitian menggunakan metode studi pustaka dengan pendekatan kualitatif deskriptif, menganalisis teori, karakteristik, serta penerapan kedua pendekatan dalam konteks pendidikan Islam. Hasil menunjukkan bahwa PjBL meningkatkan keterlibatan siswa dalam pemecahan masalah nyata, sedangkan Critical Pedagogy Islami menumbuhkan kesadaran kritis yang berlandaskan nilai spiritual dan adab. Integrasi keduanya melahirkan pembelajaran yang partisipatif, transformatif, dan relevan dengan kebutuhan abad ke-21. Studi kasus “Bumi Amanah Allah” membuktikan efektivitas model ini dalam menumbuhkan kesadaran lingkungan berbasis nilai Qur’ani. Penelitian ini berkontribusi dalam menawarkan kerangka metodologi baru bagi pengembangan pendidikan Islam kontemporer.